Knowledge About Reproductive Health Among Adolescent Girls in Selected Colleges: A Cross-sectional Study - Boominathan V.; Dhivagar S. (International Journal of Women's Health Nursing And Practices, 2023)
Introduction: Future generations' health is greatly influenced by the reproductive health of adolescent girls. For adolescent females to live healthy lives and safeguard against reproductive health issues, knowledge about reproductive health is crucial. The study's primary goal is to evaluate the pre-existing knowledge of reproductive health among adolescent girls studying in selected colleges. Methodology: A descriptive cross-sectional research with 200 teenage college-bound girls was done. The questionnaire was pre-designed and pre-tested. Information was gathered on understanding anatomy and physiology, menarche and menstrual hygiene, conception, sexual abuse, STDs, contraceptives, and sexuality and sex education. The data were statistically evaluated using Differential and Inferential statistics. Results: Knowledge of reproductive health revealed that 42.5% of respondents had a moderate understanding of anatomy and physiology, 46.5% knew about menarche and menstrual hygiene, and 7.5% knew about conception and sexual abuse. In terms of contraceptives, 41% of the girls had intermediate knowledge, 44.5% of the girls had appropriate awareness of STDs, and 58.6% of the girls had a moderate understanding of sexuality and sex education. Overall, 42.1% of the girls had moderate knowledge about reproductive health. Conclusion: The study reflects girls were having moderate knowledge regarding reproductive health. hence, many studies are required to improve the knowledge among female children.
Keywords: Adolescents; Knowledge; girl; reproductive health